Long-term feeding of the cis-9,trans-11 isomer of conjugated linoleic acid reinforces the specific immune response in rats (2009)
Several effects on the immune system have been ascribed to the cis9,trans11 conjugated linoleic acid (CLA) isomer. We studied whether feeding a diet enriched with an 80:20 CLA isomer mix of cis9,trans11 and trans10,cis12 CLA from gestation to adulthood affects the capacity of adult rats to achieve a specific immune response. Pregnant Wistar rats were fed a 1% CLA diet or a control diet beginning on d 7 of gestation. Weaned pups received the same diet as dams until they were 15 wk old. Rats from both groups were immunized with ovalbumin (OVA) when they were 9 wk old. Dietary CLA enhanced splenocyte OVA-specific proliferation by approximately 50% (P < 0.05) and decreased the mitogen-induced proliferative responses of these cells by approximately 10-20% (P < 0.05). The diminished splenocyte proliferative response was accompanied by a lower interleukin-2 secretion (P < 0.05). Long-term CLA supplementation did not increase serum, spleen, or mesenteric lymph node production of OVA-specific antibodies (Ab) or the number of spleen anti-OVA Ab-secreting cells. Interestingly, dietary CLA increased intestinal anti-OVA IgA production by approximately 75% (P < 0.05). In conclusion, a 1% CLA diet administered from gestation to adulthood enhanced specific systemic cell-mediated immunity as well as the mucosal IgA immune response, whereas it downregulated the polyclonal activation of the immune system. These data support the long-term effects of dietary cis9,trans11 CLA isomer on the immune system.